An optomicrofluidic device for the detection and isolation of drop-encapsulated target cells in single-cell format. Issue 1 (27th October 2020) - Gaikwad, R.; Sen, A. K.
Abstract : We present novel technology for the optofluidic detection and electro-coalescence-based sorting (selective isolation) of target cells in single-cell format from background cells, utilizing microdroplet encapsulation. Abstract : Single-cell analysis has emerged as a powerful method for genomics, transcriptomics, proteomics, and metabolomics characterisation at the individual cell level. Here, we demonstrate a technique for the detection and selective isolation of target cells encapsulated in microdroplets in single-cell format. A sample containing a mixed population of cells with fluorescently labelled target cells can be focused using a sheath fluid to direct cells in single file toward a droplet junction, wherein the cells are encapsulated inside droplets. The droplets containing the cells migrate toward the centre of the channel owing to non-inertial lift force. The cells present in the droplets are studied and characterised based on forward scatter (FSC), side scatter (SSC), and fluorescence (FL) signals. The FL signals from the target cells can be used to activate a selective isolation module based on electro-coalescence, using suitable electronics and a program to sort droplets containing the target cells in single-cell format from droplets containing background cells. We demonstrated the detection and isolation of target cells (cancer cells: HeLa and DU145) from mixed populations of cells, peripheral blood mononuclear cells (PBMC) + cervical cancer cells (HeLa) and PBMC + human prostate cancer cells (DU145), at a concentration range of 10 4 –10 6 ml −1 at 300 cells per s. The performance of the device is characterised in terms of sorting efficiency (>97%), enrichment (>1800×), purity (>98%), and recovery (>95%). The sorted target cells were found to be viable (>95% viability) and showed good proliferation when cultured, showing the potential of the proposed sorting technique for downstream analysis.